PELATIHAN PENGOLAHAN LIMBAH ORGANIK MELALUI SISTEM ECO-ENZYME (ECO-FERMENTOR) DAN EMBER TUMPUK ( KOMPOSTER) DI DESA KAMPUNG DURIAN, ACEH TAMIANG - Fitriani Fitriani; Beni Alfajar; Vivi Mardina; Meiliana Friska; Rahmatul Fajri (Fakultas Teknik, Universitas Samudra, 2023)
The current garbage related problems remain unresolved and will continue to increase. Household waste is one of the largest contributors of organic waste at landfills. Considering that Kampung Durian Village is a location for final waste disposal, it is necessary to provide training and assistance to the community, especially Mrs. PKK and the creative youth of Kampung Durian village in processing organic waste through an Eco-enzyme system (Eco-fermentor) and Bucket stacks (Composter) with Black soldier flies (Hermetia illucens) on a later large scale. It is hoped that this empowerment will be able to expand innovation and increase society's role in helping reduce organic waste at the landfill. The method used in this activity is the direct approach, practice, and lecture method. The approach method is carried out by recording the problems faced by partners regarding organic waste processing. The lecture method is carried out by providing information to partners about the advantages and benefits of using eco-enzymes and stacked buckets with the help of Black soldier flies in treating waste. The practical method is carried out by providing training and assistance in making eco-enzymes and stacked buckets. Based on the survey results after conducting training and direct practice in the field regarding the manufacture of Eco-Enzyme and Stacked Buckets, it shows that the level of public understanding has increased dramatically by 90%. This can be seen from the percentage of people who say they know very well about the manufacture of Eco-Enzyme and Stacked Buckets. The implementation of the program is able to provide understanding and training regarding the manufacture of Eco-Enzyme and Stacked Buckets in organic waste processing so as to reduce the amount of waste